2022
DOI: 10.1007/s12031-022-01969-0
|View full text |Cite
|
Sign up to set email alerts
|

New Target of Oxidative Stress Regulation in Cochleae: Alternative Splicing of the p62/Sqstm1 Gene

Abstract: To examine the oxidative stress and the antioxidant response of p62-Keap1-Nrf2 pathway in cochleae during age-related hearing loss (ARHL) and noise-induced hearing loss (NIHL), and then elucidate the function of full-length and variant p62/Sqstm1 (referred to here as p62) in the regulation of Nrf2 activation. Cochlear damage was assessed by analyzing auditory brainstem response (ABR) and by counting hair cells (HCs). For oxidative stress detection, the malondialdehyde (MDA) levels and 7, 8dihydro-8-oxoguanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…We have mentioned the importance of antioxidant defense by caloric restriction and antioxidant enhancement by the application of antioxidants in ARHL. Simultaneously, many studies have reported that both the caloric restriction and antioxidant applications, including Nox3 13 and P62, 94 are also promising approaches for the treatment of NIHL.…”
Section: Current Therapy For Snhlmentioning
confidence: 99%
“…We have mentioned the importance of antioxidant defense by caloric restriction and antioxidant enhancement by the application of antioxidants in ARHL. Simultaneously, many studies have reported that both the caloric restriction and antioxidant applications, including Nox3 13 and P62, 94 are also promising approaches for the treatment of NIHL.…”
Section: Current Therapy For Snhlmentioning
confidence: 99%